THE DEVELOPMENT OF METHODICAL APPROACH TO MANAGING HOUSING MAINTENANCE - E. Ermolaev; N. Kravchenko; E. Sklyrova (Вестник университета)
The existing methods of project evaluation have been considered. The methodical approach to economically viable option choice of roof cladding of a residential building has been proposed. The algorithm for calculating life-cycle cost of an apartment building has been offered. An example of the selection of appropriate embodiment of roofing has been given.